TO THE ORIGIN OF THE ETHNONYM AWAR - Hapizov, S M (History, Archeology and Ethnography of the Caucasus, 2016)
The article examines the etymology and origin of the ethnonym Awar, widely known in medieval Europe. It is still not resolved the question of the origin of the people, known as "Avars", as well as its relationship with the modern Caucasian Avars. In the article the actual Avar etymology of the ethnonym Awar, as a people, who came from the "wasteland" (translation variants: "virgin lands" or "Steppe"). It is also proposed to distinguish between questions of origin of the Caucasian and Central Asian Awar.